2009
DOI: 10.1029/2008ja013508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of AMIE‐modeled and Sondrestrom‐measured Joule heating: A study in model resolution and electric field–conductivity correlation

Abstract: [1] Joule heating by high-latitude ionospheric electric fields is thought to be underestimated by models, and it has been conjectured that the source of the underestimation is ''electric field variability,'' which is often defined as electric field structure below the resolution of the model. We investigate this and related issues by (1) comparing the Joule heating measured by the Sondrestrom incoherent scatter radar during a 40 h period containing a storm with that modeled by the Assimilative Mapping of Ionos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Some of the more recent publications include those by Johnson and Heelis (2005), Zhang et al (2005), Vasyliunas and Song (2005), McHarg et al (2005), Hernandez et al (2005), Knipp et al (2005), Weimer (2005, Palmroth et al (2006), Rosenquist et al (2006, Wilson et al (2006), Fang et al (2007a, Deng and Ridley (2007), Rae et al (2007), Fujiwara et al (2007), , Hardy et al (2008), Deng et al (2008), Golovchanskaya (2008, Emery et al (2008), Matsuo and Richmond (2008), Cosgrove et al (2009), Aikio andSelkälä (2009), Burke et al (2010a, b); and references therein.…”
Section: Brief History Of Upper Atmospheric Storm Researchmentioning
confidence: 95%
“…Some of the more recent publications include those by Johnson and Heelis (2005), Zhang et al (2005), Vasyliunas and Song (2005), McHarg et al (2005), Hernandez et al (2005), Knipp et al (2005), Weimer (2005, Palmroth et al (2006), Rosenquist et al (2006, Wilson et al (2006), Fang et al (2007a, Deng and Ridley (2007), Rae et al (2007), Fujiwara et al (2007), , Hardy et al (2008), Deng et al (2008), Golovchanskaya (2008, Emery et al (2008), Matsuo and Richmond (2008), Cosgrove et al (2009), Aikio andSelkälä (2009), Burke et al (2010a, b); and references therein.…”
Section: Brief History Of Upper Atmospheric Storm Researchmentioning
confidence: 95%
“…Most ignore the effects of variable conductivity. Cosgrove et al [2009] found that an anticorrelation between spatial fluctuations in conductance and squared electric field may partially compensate for the effects of the field variability.…”
Section: Introductionmentioning
confidence: 99%
“…The computational efficiency of the empirical models makes them favorable in space weather forecasting applications; however, they cannot model the short‐lived, small‐scale perturbations, that is, PI and MI FACs, that occur during the interaction of solar wind with the Earth's magnetosphere (Boudouridis et al, ; Deng & Ridley, ; Weimer, ). Various studies (Codrescu et al, ; Cosgrove et al, ) have shown that the majority of Joule heating rate comes from such transient, localized electric field perturbations making the MHD‐driven electrodynamics a better tool to investigate the coupling between magnetosphere‐ionosphere‐thermosphere systems.…”
Section: Discussionmentioning
confidence: 99%